Genomic characterization of response to chemoradiation in urothelial bladder cancer. Issue 23 (1st August 2016) - Desai, Neil B.; Scott, Sasinya N.; Zabor, Emily C.; Cha, Eugene K.; Hreiki, Joseph; Sfakianos, John P.; Ramirez, Ricardo; Bagrodia, Aditya; Rosenberg, Jonathan E.; Bajorin, Dean F.; Berger, Michael F.; Bochner, Bernard H.; et al.
Abstract : BACKGROUND: The authors characterized the genetic landscape of chemoradiation‐treated urothelial carcinoma of the bladder (UCB) with the objective of identifying potential correlates of response. METHODS: Primary tumors with (n = 8) or without (n = 40) matched recurrent tumors from 48 patients who had non‐metastatic, high‐grade UCB and received treatment primarily with chemoradiation were analyzed using a next‐generation sequencing assay enriched for cancer‐related and canonical DNA damage response (DDR) genes. Protein expression of meiotic recombination 11 homolog (MRE11), a previously suggested biomarker, was assessed in 44 patients. Recurrent tumors were compared with primary tumors, and the clinical impact of likely deleterious DDR gene alterations was evaluated. RESULTS: The profile of alterations approximated that of prior UCB cohorts. Within 5 pairs of matched primary‐recurrent tumors, a median of 92% of somatic mutations were shared. A median 33% of mutations were shared between 3 matched bladder‐metastasis pairs. Of 26 patients (54%) who had DDR gene alterations, 12 (25%) harbored likely deleterious alterations. In multivariable analysis, these patients displayed a trend toward reduced bladder recurrence (hazard ratio, 0.32; P  = .070) or any recurrence (hazard ratio, 0.37; P  = .070). The most common of these alterations, ERCC2 (excision repair cross‐complementation group 2) mutations, were associated with significantly lower 2‐year metastatic recurrence (0% vs 43%; log‐rank P  = .044). No impact of MRE11 protein expression on outcome was detected. CONCLUSIONS: A similar mutation profile between primary and recurrent tumors suggests that pre‐existing, resistant clonal populations represent the primary mechanism of chemoradiation treatment failure. Deleterious DDR genetic alterations, particularly recurrent alterations in ERCC2, may be associated with improved chemoradiation outcomes in patients with UCB. A small sample size necessitates independent validation of these observations. Cancer 2016;122:3715‐23. © 2016 American Cancer Society . Abstract : Targeted sequencing of tumors from patients with urothelial carcinoma of the bladder undergoing organ preservation using chemoradiation demonstrates a strikingly similar pattern of genomic alterations between organ‐confined recurrences and primary tumors, indicating that pre‐existing, treatment‐resistant clonal populations represent the primary mechanism of treatment failure for this approach. In addition, deleterious alterations within genes involved in DNA damage response associate with a trend toward improved outcomes after chemoradiation.